Exploring root rot pathogens in wheat-pea rotations in Kansas - Smith, Nathan; Mangel, Dylan; Beyer, Nick; Ranabhat, Nar; Davis, Mark; Bruce, Myron; Rupp, Jessica L. (My University, 2019)
In 2018, over 277,000 bushels of wheat were produced on 7.7 million acres of land in Kansas alone. Based on the price of wheat by the end of 2018, this accounted for $1.44 million. This wheat is normally rotated with soybeans or fallow, but recent interest has arisen regarding the growth of peas in northern Kansas. As of 2019, there are both research and commercial growing operations underway. Many plant diseases have been especially prevalent during the summer because of the high rainfall and heat. In order to assess the severity of pea disease in Kansas, as well as explore potential interconnectivity between wheat and pea pathogens, a survey was conducted, and efforts were made to isolate and culture fungal pathogens of both wheat and pea.
Keywords: USDA NIFA 2019-67032-29071